Rapid growth of firms after recession: evaluating financial results - V. V. Spitsin; M. A. Hasanov; O. B. Yudakhina (Управление)
In the conditions of economic stagnation and crisis events, many Russian enterprises found themselves in a long-term recession. When the economic situation improves, some of such firms demonstrate rapid sales growth (restarting growth). This article aims to comprehensively assess the financial results of the restarting growth of the Russian enterprises. The sample includes 2,198 Russian industrial companies that found themselves in the recession, some of them showed the sales growth in 2016–2021. The sample has been divided into 5 groups: four groups of the companies by type of the restarting growth and a group of the companies that did not show it. To compare financial indicators between them, we have used dispersion analysis. We have found that all the groups of the firms with the restarting growth significantly improved their financial performance (size, turnover, profitability) and outperformed the group of the companies that did not show the restarting growth. However, they have problems with financial sustainability. The groups of the firms with the long[1]term restarting growth are riskier. Consequently, most firms finance the restarting growth with borrowed funds. These results should be considered in the current conditions, when the Russian Federation (hereinafter referred to as RF) is undergoing significant tightening of monetary policy. The growth of interest rates will become a strong obstacle for the continuation of the restarting growth and actualise the problem of the financial stability of the growing firms. The paper proposes several recommendations to investors, firm managers and regulatory authorities based on the current economic situation in the RF.